The Effectiveness of Intradialytic Exercise in Reducing Fatigue among Hemodialysis Patients Based on Roy Adaptation Model - Syarief Hidayatullah Bahri; Priyanto Priyanto (Madago Nursing Journal, 2026)
Background: Fatigue is one of the most common and distressing problems among hemodialysis patients, significantly affecting their quality of life and adherence to treatment. This condition arises from physiological and psychological imbalances experienced during the hemodialysis process. Within the framework of the Roy Adaptation Model, fatigue is understood as a maladaptive response to prolonged stressors, while intradialytic exercise can function as an adaptive mechanism to enhance positive adjustment. Methods: This conceptual study employed a literature-based review approach by synthesizing evidence from recent national and international publications from 2022 to 2025. Thematic analysis was conducted based on the four adaptive modes of the Roy Adaptation Model: physiological, self-concept, role function, and interdependence. Results: The synthesis revealed that intradialytic exercise, which refers to physical activity performed during hemodialysis, effectively reduces fatigue levels by improving muscle perfusion, enhancing cardiovascular function, and stabilizing hormonal balance. This adaptive intervention supports physiological stability and promotes better psychosocial adjustment in hemodialysis patients. Conclusion: Intradialytic exercise serves as an effective adaptive nursing intervention to minimize fatigue and improve the overall quality of life in hemodialysis patients. These findings provide both theoretical and practical implications for developing comprehensive and sustainable nursing strategies grounded in the Roy Adaptation Model. KEYWORDS: Fatigue; Hemodialysis; Intradialytic Exercise; Roy Adaptation Model